Arabic-Indonesian Dictionary: Comparison of Digital Dictionary and Printed Dictionary - Rizqia, Asa Qubaila Sitta Zidna; Maylana, Aninda Nisa; Luthfi, Khabibi Muhammad (Al-Ma‘rifah, 2022)
The Arabic-Indonesian Digital Dictionary (KDAI, lit Kamus Digital Arab Indonesia) available in the play store and the Printed Arabic-Indonesian Dictionary (KCAI, lit Kamus Cetak Arab Indonesia) by Muhammad Yunus are two dictionaries that provide two languages ​​with different publications. Digital and printed dictionaries and the comparison of the two dictionaries based on the ideal dictionary even though the number of enthusiasts is other. This study uses a descriptive qualitative approach with the method of literature. The digital dictionary is the most in-demand one, with 1,000,000 downloads. In contrast, the print dictionary by Muhammad Yunus is inversely proportional to the fact that few users know this printed dictionary. The results of this study are from the type of KDAI and KCAI; there are similarities in nuqṭat al-iṭlāq and ‘adad al-lughāt. In terms of meaning, KDAI includes a language dictionary, and KCAI consists of a translation dictionary. The lemma part of the second dictionary has a different number of lemmas, and also, in the explanation of each entry, there are differences. KDAI uses a collocation system, while KCAI uses a definition system. Based on compiling KDAI using software entry, KCAI uses arrangements based on pronunciation.